Utilizing Nanoparticle Catalyzed TMB/H2 O2 System for Determination of Aspirin in Exhaled Breath Condensate - Samineh Mohammadzadeh Abachi; Homa Rezaei; Maryam Khoubnasabjafari; Vahid Jouyban-Gharamaleki; Elaheh Rahimpour; Abolghasem Jouyban (Tabriz University of Medical Sciences, 2023)
Background: According to the poison center data for most countries, more than thousands of people's exposure to aspirin or salicylate-containing products. So, this work aimed was to offer a rapid colorimetric method for monitoring aspirin concentration in exhaled breath condensate (EBC). Methods: A method based on a redox reaction catalyzed by nanoparticles was validated for the analysis of aspirin. 3,3 ,5,5 -Tetramethyl benzidine /H2 O2 and sodium dodecyl sulfate modified silver nanoparticles were used as the redox reagents and catalyst, respectively. Results: Detection mechanism of aspirin using this system is based on the inhibitory effect of aspirin on the signal intensity of the colorimetric systems. Since the decrement in signal intensity was proportional to aspirin level, a colorimetric method was proposed for its quantification in EBC samples. This method shows a linear relationship with aspirin concentration in the range of 10‒250 mg.L−1 with a relative standard deviation of < 3.5%. Conclusion: This method has great potential for aspirin determination due to some features such as high reliability, and fast response time.